Therapy for persons deprived of liberty in Poland: Insights from statistical data - Kwieciński, Adam; Polak-Kruszyk, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In this article, data concerning the therapeutic system of imprisonment in Poland for the years 1999–2023 is analysed. Changes in the prison population and the number of convicts within the therapeutic system are presented, taking into account different categories of convicts, types of penitentiaries, and whether the therapy was conducted within or outside specialized therapeutic wards. The analysis begins with data from 1999, the first full year of the new Polish Executive Penal Code, which established the therapeutic system as a separate method of serving the penalty of deprivation of liberty (alongside the regular system and programme system). The aim of this publication is to present the evolution of the therapy of persons deprived of liberty in Poland over the past 25 years, focusing on quantitative, structural, and organizational aspects. This paper highlights the most important aspects of the therapeutic system in Poland, which have been documented in official statistical publications.
Keywords: therapeutic system; therapeutic wards; prisoners; mental disorders; addictions; disability; Executive Penal Code; prison therapy; penitentiary statistics; evolution of penal therapy